2019
DOI: 10.1108/ajems-10-2018-0311
|View full text |Cite
|
Sign up to set email alerts
|

Exploring retention factors and job security of nurses in Gauteng public hospitals in South Africa

Abstract: Purpose The purpose of this paper is to investigate the relationship between employee retention and job security and the impact of retention factors on the job security of nurses in public hospitals in South Africa. The retention of nurses is essential in public hospitals in South Africa. It is therefore critical that retention strategies are primed to ensure the job security of nurses. Design/methodology/approach The study is quantitative in nature, adopts a cross-sectional approach and is set within a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…The results of this analysis further support findings by Botha, Bussin, and De Swardt (2011) that an organisation's people strategy delivers on the employer brand promise where the value proposition that the organisation articulates is reflected by the attention paid to people management strategies. Thus, the need for an integrated approach to the management of talent in an effort to attract and retain talent has been recognised by many authors (Azma et al, 2019;Dhanpat, Manakana, Mbacaza, Mokone, & Mtongana, 2019;Ncube, 2018;Schutte, Barkhuizen, & Van der Sluis, 2015). Furthermore, Crowley-Henry, Benson and Al Ariss (2019) emphasised that, in order to attract, develop and retain key employees in organisations, it is important to understand the nature and context of their careers.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this analysis further support findings by Botha, Bussin, and De Swardt (2011) that an organisation's people strategy delivers on the employer brand promise where the value proposition that the organisation articulates is reflected by the attention paid to people management strategies. Thus, the need for an integrated approach to the management of talent in an effort to attract and retain talent has been recognised by many authors (Azma et al, 2019;Dhanpat, Manakana, Mbacaza, Mokone, & Mtongana, 2019;Ncube, 2018;Schutte, Barkhuizen, & Van der Sluis, 2015). Furthermore, Crowley-Henry, Benson and Al Ariss (2019) emphasised that, in order to attract, develop and retain key employees in organisations, it is important to understand the nature and context of their careers.…”
Section: Discussionmentioning
confidence: 99%
“…Employee turnover is a problem faced in international human resource management at this time.Moreover; the knowledge transfer issue due to the aging workforce and talent crisis is more acute in developed countries as compared to developing countries especially in upstream sector which is suffering the most (Sumbal et al 2018).As an employer, the STM plays crucial factor in order to ensure employee retain in the company.A. Harhara et al, ( (Dhanpat et al 2019) also found, STM practice (training and development) was the stronger factor for job security that contributed to job retention among workers.Meanwhile, STM practices as a whole were positively related to employee's retention in Oil & Gas company (Fathaniy 2011). Hence, the study argues that STM are related to job retention which formulates hypothesis as below:…”
Section: Strategic Talent Management and Job Retentionmentioning
confidence: 95%
“…Talent management is conducted to maximise an organization's overall efficiency or to serve as a competitive advantage. Concerned with the management of the firm's strategic human capital resources, which are viewed as rare, valuable, and difficult to replicate from the firm's resourcebased view (RBV), this practise of strategic workforce differentiation is expected to add value to the organisations that implement it, and doing so requires significant management effort and expense (Chang & Busser, 2020;Dhanpat et al, 2019;DiPietro et al, 2019;Matongolo et al, 2018;Mukherjee et al, 2019). The overarching principle of talent management is to maximise the value of talent as a distinct resource for the benefit of the organisation.…”
Section: Literature Review What Is Talent Management (Tm)?mentioning
confidence: 99%